ISHLAB CHIQARISH KORXONALARIDA LOGISTIKA XIZMATINI RIVOJLANTIRISHNING DOLZARB MASALALARI (Marketing Journal, 2026)
AbstractThis article analyzes the current issues of developing logistics services inmanufacturing enterprises based on a systemic approach. The study scientificallysubstantiates the changes in the role and functional content of logistics in the contextof the evolution of production systems, industrial revolutions, and the digital economy.Particular attention is paid to ensuring the integrity of the production and logisticsenvironment, synchronizing material and information flows, optimizing inventories,and reducing logistics costs. Furthermore, the priority directions for the effectiveorganization of logistics services in enterprises are justified, including theimplementation of digital technologies, the application of lean production principles,strengthening integration among supply chain participants, and the formation of aprocess-oriented management system.Keywords: production logistics, production-logistics system, supply logistics,distribution logistics, resource movement logistics, transport logistics, internalproduction flows, warehousing, digital platforms, automated control systems.